UNDERSTANDING SOCIAL ENTERPRISES IN INDONESIA: - Rostiani, Rokhima; Paramita, Widya; Audita, Handini; Virgosita, Risa; Budiarto, Teguh; Purnomo, Boyke R. (Journal of Indonesian Economy and Business, 2014)
Entrepreneurship has been one of the biggest growth topics in the past decades. Someentrepreneurs engage in socially active activities that are strongly embedded in their entrepreneurialactivities and are known as social entrepreneurship. This research maps the presence ofsocial enterprises in Indonesia by investigating the personal and organizational contexts of thesocial entrepreneurs. Qualitative research was conducted by engaging in in-depth interviewswith 8 social enterprises in Indonesia. The findings of this research result in a unique andinteresting map of the presence of the social entrepreneurs that contributes significantly to theextant literatures of social entrepreneurship.* We would like to thank the anonymous reviewer andparticipants in the APCBSS 2014 Conference for theinsightful discussions, comments and advice for thispaper.Keywords: Social entrepreneurship, small and medium enterprise, entrepreneurship, strategy